Perancangan Desain User Interface Aplikasi KABITA Untuk Menginformasikan Kuliner Street Food Kota Bandung - Diwan Setiawan; Sri Wulandari (ArtComm, 2020)
Bandung is a city that has a variety of culinary, it makes this city as a culinary tourism destination that highly demanded by both domestic and foreign tourists. Based on data from the Department of Culture and Tourism of Bandung, Bandung has a legendary street food culinary that is highly favored by culinary enthusiasts who visit this city. Street food culinary is snacks that have been around for a long time with authentic flavors and stories behind, some of popular street food culinary are bandros, combro, colenak, ketan bakar, cireng ​​and others. The rapid development of culinary potential in this city has caused many new street foods that enriches culinary diversity in Bandung so that culinary enthusiasts need an information media contains of information about culinary in this city, especially authentic street food culinary which is starting to be hard to find. Through qualitative methods and data collection techniques by means of field studies such as observation, interviews and questionnaires, it is necessary to design an application-based information media. The final results of this research is user interface design for the media that informs Bandung street food culinary. Inspired by the word kabita which comes from Sundanese means tempted to taste food, was chosen as the name of the application that informs culinary street food in the city of Bandung that aims to facilitate culinary enthusiasts to get that information